2019
DOI: 10.1111/maec.12531
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term temporal and spatial patterns in bioeroding sponge distribution at the Abrolhos Bank, Brazil, Southwestern Atlantic

Abstract: Bioeroding sponges belong to the most dominant bioeroders, significantly contributing to the erosion of coral reefs. Some species are tolerant or even benefit from environmental conditions such as ocean warming, acidification, and eutrophication. In consequence, increases in sponge bioerosion have been observed on some coral reefs over the last decades. The Abrolhos Bank is the largest coral reef system in the South Atlantic. It has been affected by sedimentation, eutrophication, overfishing, and climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, higher coral covers were observed on nearshore walls, which is consistent with previous observations of persistent coral assemblages under turbid conditions [ 20 ]. The relatively high abundance of sponges and CCA on walls seems related to their high tolerance to low light regimes [ 59 , 60 ]. Offshore, macroalgal cover was minimal, while some nearshore reefs were dominated by unpalatable forms (e.g., Canistrocarpus , Lobophora ) that are weakly controlled by herbivores fishes [ 61 , 62 ] due to either structural or chemical defenses.…”
Section: Discussionmentioning
confidence: 99%
“…However, higher coral covers were observed on nearshore walls, which is consistent with previous observations of persistent coral assemblages under turbid conditions [ 20 ]. The relatively high abundance of sponges and CCA on walls seems related to their high tolerance to low light regimes [ 59 , 60 ]. Offshore, macroalgal cover was minimal, while some nearshore reefs were dominated by unpalatable forms (e.g., Canistrocarpus , Lobophora ) that are weakly controlled by herbivores fishes [ 61 , 62 ] due to either structural or chemical defenses.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal variability of sponges has previously been described from the Caribbean (Zea, 1994;Wulff, 2006a), Indo-Pacific (Biggerstaff et al, 2017;Rovellini et al, 2019), tropical Atlantic (Kelmo et al, 2013;de Moraes et al, 2019), Mediterranean (Koopmans & Wijffels, 2008;Di Camillo et al, 2012) and Great Barrier Reef (Ramsby et al, 2017), but there have been no studies from the Indian Ocean. From these earlier studies, multiple biotic and abiotic factors, including macroalgal competition (Ávila et al, 2015;Ramsby et al, 2017), seawater temperature (Carballo et al, 2008;Kelmo et al, 2013), salinity (Corriero et al, 2007;Longo et al, 2015) and cyanobacterial blooms (Butler et al, 1995;Stevely et al, 2010), have been reported to correlate with sponge temporal variability.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced spatial competition between corals and sponges provided sponges more space to proliferate. Furthermore, a six-year study on South Atlantic sponge reefs showed that the abundance of bioeroding sponges increased over time, which was correlated with elevated sea surface temperature (de Moraes et al, 2019). However, while multiple studies have been conducted on the temporal variability of reef sponges, few studies have explored temporal variation in lagoon-inhabiting sponges.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, multiple studies have investigated the impacts of climate change (Massaro et al, 2012;Bennett et al, 2017;Ramsby et al, 2018) and eutrophication on tropical sponges. While there have been multiple evidences indicating that sponges are more likely tolerant to other dominant calcifying benthic taxa such as corals (Bell et al, 2013;Kelmo et al, 2013;de Moraes et al, 2019), the mechanisms underlying the tolerance or acclimation of sponges (mostly bioeroding species) to climate change (Fang et al, 2014;Bell et al, 2018) and eutrophication are relatively unknown. Future work should therefore be focussed on the understanding the specific physiological and cellular mechanisms, which enable sponges to acclimate to enviromental stress.…”
Section: Future Directionsmentioning
confidence: 99%
“…The temporal variability of sponges has previously been described from the Caribbean (Zea, 1994;Wulff, 2006a), Indo-Pacific (Biggerstaff et al, 2017;Rovellini et al, 2019), tropical Atlantic (Kelmo et al, 2013;de Moraes et al, 2019), Mediterranean (Koopmans & Wijffels, 2008;Di Camillo et al, 2012) and Great Barrier Reef (Ramsby et al, 2017), but there have been no studies from the Indian Ocean. From these earlier studies, multiple biotic and abiotic factors, including macroalgal competition (Ávila et al, 2015;Ramsby et al, 2017), seawater temperature (Carballo et al, 2008;Kelmo et al, 2013), salinity (Corriero et al, 2007;Longo et al, 2015) and cyanobacterial blooms (Butler et al, 1995;Stevely et al, 2010), have been reported to correlate with sponge temporal variability.…”
Section: Introductionmentioning
confidence: 99%